The Influence of Accounting Information Systems on the Financial Performance of Business Actors in E-Commerce - Permatasari, Uut; Yanthi, Merlyana Dwinda (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to examine the influence of accounting information systems, measured using proxy measures of perceived usefulness and perceived ease of use, on the financial performance of e-commerce businesses. This topic was chosen due to the issue of diverse understandings of business actors regarding accounting information systems in e-commerce, which are considered to influence the effectiveness of financial performance. The method used is a quantitative approach with a survey technique through questionnaires distributed to business actors. Data analysis used multiple linear regression with the SPSS program. The results of the study indicate that accounting information system variables, measured using proxy measures of perceived usefulness and perceived ease of use, have a positive effect on the financial performance of e-commerce businesses.